A combined oxidation and salt-thermal approach to converting copper scraps to copper oxides as energy storage materials. (20th October 2021) - Zhao, Haijia; Zhao, Zhuqing; Qu, Jiakang; Chen, Xiang; Zhou, Fengyin; Xie, Hongwei; Wang, Dihua; Yin, Huayi
Abstract: Recycling and valorization of copper (Cu) scraps are of great strategic significance due to the increasing need for Cu metals/alloys and limited Cu resources. However, the traditional recycling method that remelts Cu scraps is difficult to deal with the fine Cu powder waste that is oxidized easily during the manufacturing process. Herein, we develop a green salt-thermal method to convert Cu scraps-derived CuO into Cu2 O powders for energy storage materials. First, the Cu waste was oxidized to precursory CuO (P-CuO) in the air. Second, the P-CuO was transformed into Cu2 O powders whose particle size was 100 times smaller than that of CuO through self-thermal decomposition in molten salt without any reducing agent. In addition, the Cu2 O can be re-oxidized to CuO (R-CuO) while maintaining the same particle size as Cu2 O. Third, the obtained Cu2 O and R-CuO can be used for energy storage materials: the Cu2 O served as an anode material and delivered a specific capacity of 312.9 mA h g −1 at 100 mA g −1 after 200 cycles for lithium-ion batteries, and R-CuO delivered a specific capacity of 804.1 mA h g −1 at 100 mA g −1 for lithium-ion batteries and 196.3 mA h g −1 at 100 mA g −1 for sodium-ion batteries after 200 cycles. Moreover, the R-CuO is a promising electrode for pseudo supercapacitors and delivered a specific capacity of 493 F g −1 at 5 A g −1 in a three-electrode cell. Overall, this paper provides a green method to repurpose heavily oxidized Cu scraps. Graphical abstract: Image 1 Highlights: A self-driven salt-thermal approach was developed to recycle Cu scraps. CuO was converted to Cu2 O in molten salt without using reducing agents. Molten salt offers a water- and oxygen-free medium to allow the reduction reaction. The particle size of Cu2 O was 100 times smaller than the CuO precursor. Cu scrap-derived Cu2 O and CuO are promising energy storage materials.